Genomic Meningococcal Load in the Nasopharynx of Children with Meningococcal Disease. Issue 5 (May 2016) - Bourke, Thomas W.; McKenna, James P.; Coyle, Peter V.; Fairley, Derek J.; Shields, Michael D.
Abstract : This study demonstrates the feasibility of using quantitative real time PCR to measure genomic bacterial load in the nasopharynx of children with invasive meningococcal disease and shows that these loads are exceptionally high (median 6.6 × 10 5 (range 1.2 × 10 5 –1.1 × 10 8 ) genome copies of Neisseria meningitidis per swab). Abstract : Supplemental Digital Content is available in the text.